2011
DOI: 10.1016/j.physletb.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Yangian symmetry in deformed WZNW models on squashed spheres

Abstract: We introduce a deformation of the Wess-Zumino-Novikov-Witten model with threedimensional squashed sphere target space. We show how with an appropriate choice of Wess-Zumino and boundary terms it is possible to construct an infinite family of conserved charges realizing an SU(2) Yangian. Finally we discuss the running of the squashing parameter under renormalization group flow.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 54 publications
5
85
0
Order By: Relevance
“…The squashed sigma model is not conformal and hence we have to add the Wess-Zumino (WZ) term. We have already shown that the SU(2) L Yangian algebra is still preserved even after adding the WZ term [23]. However, the quantum affine algebra in the presence of the WZ term has not been investigated yet.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The squashed sigma model is not conformal and hence we have to add the Wess-Zumino (WZ) term. We have already shown that the SU(2) L Yangian algebra is still preserved even after adding the WZ term [23]. However, the quantum affine algebra in the presence of the WZ term has not been investigated yet.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Although the squashed sigma models are well known as an integrable model of the trigonometric class, it has been shown that a Yangian symmetry Y (sl (2)) is realized even after the squashing in a series of works [22][23][24] (For a short summary see [25]). This result may sound curious.…”
Section: Introductionmentioning
confidence: 99%
“…Although deformed target spaces are not represented by symmetric cosets 2 and there is no general prescription to argue the integrability, many techniques have been developed and various aspects have been revealed. Especially for squashed S 3 , the Lax pair was presented in [22] and the classical integrable structure has been elaborated in the subsequent works [23][24][25][26][27][28][29][30][31][32][33][34]. As a possible way toward higher-dimensional cases, the Yang-Baxter sigma model approach was proposed by Klimcik [17][18][19].…”
Section: Jhep06(2014)135mentioning
confidence: 99%
“…Deformations of S 3 and AdS 3 have been well investigated [8][9][10][11][12][13][14][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. 1 A systematic way is the Yang-Baxter sigma model approach proposed by Klimcik [11][12][13].…”
Section: Jhep10(2015)185mentioning
confidence: 99%